The Clinical Effectiveness of Mesotherapy in Refractory Chronic Migraine - Ozyigit, Elif; Zure, Mert; Topçu, Esra; UÇAR, MEHMET FATİH (Galenos Yayınevi, 2025)
Aim: This study aimed to evaluate the clinical effectiveness of mesotherapy in patients with refractory chronic migraine (CM). The goal was to determine its impact on pain frequency, duration, and intensity and on analgesic use, thereby informing alternative therapeutic strategies for this population. Methods: This retrospective cohort study included 27 patients diagnosed with CM. These patients received mesotherapy injections containing 2 mL of 1% lidocaine, 40 mg of piroxicam in 2 mL, and 100 U of calcitonin in 1 mL at specific anatomical sites, including the glabella, supraorbital notch, infraorbital foramen, preauricular, postauricular, and temporal masseter, fronto-occipital, and trapezius muscle trigger points. Assessment parameters included the frequency of painful days per month (PDs), the number of analgesics per month (NoA), the duration of attacks per month (DoA), and the patients’ visual analogue scale (VAS) scores. Evaluations were conducted before treatment and at 4, 8, and 12 weeks post-treatment. Results: Significant improvements were observed in the NoA, DoA, PD, and VAS scores at 4 and 8 weeks post-treatment, compared with pre-treatment values. Although efficacy declined by week 12, scores remained higher than baseline. No adverse events were reported. Conclusion: Mesotherapy appears to be an effective treatment for CM, with notable improvements in pain frequency, duration, and severity and a reduced need for analgesics over 12 weeks. To more thoroughly assess this efficacy, large-scale, prospective, randomized controlled studies are required.
Keywords: Analgesics; Mesotherapy; Migraine Disorders; Pain; Piroxicam